Stingless bees (Apidae: Meliponini) at risk in western Mexico. (7th April 2022) - Reyes‐Gonzalez, Alejandro; Mora, Francisco; Porter‐Boland, Luciana; Ramírez, M. Isabel; del‐Val, Ek
Abstract: The current global pollinator crisis highlights the need to investigate the diversity and distribution of ecologically and socially relevant taxa such as tropical stingless bees. We analyzed the diversity and composition of stingless bee (Meliponini) communities at a regional scale in west‐central Mexico using an extensive direct search along an altitudinal gradient encompassing different climate and vegetation types. Our hypothesis was that meliponine bee diversity would be greater in tropical warmer. We found a total of 14 meliponine bee species, including two new records for the region. We identified three types of bee assemblages: one in hot lowland climates with tropical dry forest vegetation, one in temperate highland climates with mixed oak‐pine forest vegetation, and one in the warm ecotone with mixed subdeciduous forest vegetation between the hot and temperate zones. As expected, the lowland assemblage in the tropical dry forest vegetation had the greatest diversity (11 species). In the warm ecotone, meliponine species from temperate highlands and hot lowland habitats converged; this region should therefore be considered a high conservation priority area. Fifty percent of the meliponine bees found are endemic and have a very low incidence, suggesting that their populations may be endangered. Given the extensive and ongoing change of land use to avocado plantations in the warm ecotone and temperate highlands with mixed oak‐pine forest vegetation cover, specific conservation plans should be generated to conserve the natural ecosystems and this important native pollinator group. Abstract in Spanish is available with online material. Abstract : We found a total of 14 stingless bee species, including two new records for the region. We identified three types of bee assemblages: one in hot lowland climates with tropical dry forest vegetation, one in temperate highland climates with mixed oak‐pine forest vegetation, and one in the warm ecotone with mixed subdeciduous forest vegetation between the hot and temperate zones. The habitats of meliponine bee in temperate highland and warm ecotone require urgent actions to safeguard the conservation of their natural ecosystems and of this important group of native pollinators. Resumen: La actual crisis mundial de los polinizadores enfatiza la necesidad de investigar la diversidad y distribución de taxones relevantes desde el punto de vista ecológico y social. Analizamos la diversidad y composición de las comunidades de abejas sin aguijón (Meliponini) a escala regional en el centro‐oeste de México. Se realizó una búsqueda directa en un gradiente altitudinal considerando clima y tipos de vegetación. Nuestra hipótesis era que la comunidad de meliponinos sería más diversa hacia las regiones más cálidas. Encontramos un total de 14 especies de meliponinos, incluidos dos nuevos registros para la región. Identificamos tres tipos de ensamblajes de abejas: uno en tierras bajas de clima caliente y árido, uno en tierras altas de clima templado y uno en el ecotóno cálido entre zonas calientes y templadas. La zona de tierras bajas de clima caliente y árido concentró más especies (11 meliponinos) concordando con la hipótesis planteada. En el ecotono cálido convergen especies de hábitat templado de tierras altas y de tierras bajas de clima caliente, sugerimos debe considerarse área prioritaria de conservación. El cincuenta por ciento de meliponinos encontrados en este estudio son endémicos y tienen una incidencia muy baja, lo que sugiere que sus poblaciones pueden estar en peligro. Dado el extenso y continuo cambio de uso de la tierra a plantaciones de aguacate en el ecotono cálido y las tierras altas templadas, se deben generar planes de manejo específicos para conservar los ecosistemas naturales y este importante grupo de polinizadores nativos.